Genealogical analysis and identification of donors and sources of valuable breeding traits in the sweet cherry gene pool (overview) - O. V. Eremina (Труды по прикладной ботанике, генетике и селекции, 2019)
A comprehensive study of the Prunus avium (L.) L. gene pool has identified sources of important breeding traits which can be recommended for the use in programs aimed at breeding new varieties and clonal rootstocks of sweet cherry. Of special importance are the sources of such useful breeding traits as large fruit size (e.g., varieties 'Valerii Chkalov', 'Hedelfingen', 'Krupnoplodnaya', 'Emperor Francis', 'Donchanka', 'Amulet', 'Aleksandriya', 'Vasilisa', 'Yaroslavna', 'Bigarreau Burlat', etc.); self-fertility ('Whiis Gold', 'Camelia', 'Lapins', 'Sweetheart', 'Skeena', 'Staccato', 'Shelen', 'Stella', 'Newstar', 'Sunburst', 'Summit', 'John Innes 2420'), resistance to coccomicosis ('Valerii Chkalov', Trieste der Markt', 'Drogans Gelbe', 'Bigarreau Gaucher', 'Napoleon', 'Tatarskaya chernaya', 'Emperor Francis', 'Skeena', 'Amulet', 'Hedelfingen', 'Generalskaya', 'Euphoria', etc.), and resistance to fruit cracking ('Alaya', 'Amazonka', 'Amulet', 'Viola', 'Donetskaya krasavitsa', 'Donetskiyi velikan', 'Donchanka', 'Hedelfingen', 'Contrastnaya', 'Merton Bigarreau', 'Proshalnaya', 'Sweetheart', etc.) Some genotypes have been identified as complex sources of valuable traits. For instance, these are varieties 'Lapins', 'Skeena', 'Sweetheart', 'Hedelfingen', 'Emperor Francis', 'Valerii Chkalov', 'Drogans Gelbe' and some others. The genealogical analysis of sweet cherry genotypes made it possible to identify the varieties 'Lapins', 'Skeena', 'Sweetheart' and 'Krupnoplodnaya' as complex donors combining sets of such important breeding traits as productivity, late maturity of fruits, large fruit size, high quality taste of fruit and selffertility. The varieties 'Bigarreau Burlat', 'Bigarreau de Germersdorf', 'Valerii Chkalov', 'Stella', 'Van', 'Vittoria', 'Drogans Gelbe', Daybera black' are regarded as "hidden" donors, as the transferred traits do not manifest themselves in the phenotype, but can be traced in their progeny.